The Relationship between Age and Activity of Daily Living withthe Fall Risk of Patients in Geriatric Outpatient Installation - Deniro, Agustin Junior Nanda; Sulistiawati, Nuniek Nugraheni; Widajanti, Novira (Jurnal Penyakit Dalam Indonesia, 2017)
Introduction. Fall is one of the physical problems that happened quite frequently and resulted in morbidity and mortality of old people. There are several factors related to fall risk, among others are age and independence in activity of daily living. Methods. This research is an observational analytical study with cross sectional approach, by collecting free variable data (age and activity of daily living) through interview and Barthel index score, dependent variable (fall risk) by direct observation using Timed Up and Go test that analyzed by Rank Spearman correlation test. The number of samples with incidental sampling technique was 55 patients in Geriatric Outpatient Installation RSUD Dr Soetomo Surabaya for the period of August – October 2017. Results. Bivariate analysis showed that there was a correlation between age and fall risk (r = 0.334, p <0.05) and there was a relationship between activity of daily living with fall risk (r = - 0.460, p <0.05 ) of patient in Geriatric Outpatient Installation RSUD Dr Soetomo Surabaya period August - October 2017. Conclusion. There is a significantly low and equivalent relationship between age and fall risk and significantly low and unequal relationship between activity of daily living and fall risk of patients in Geriatric Outpatient Installation RSUD Dr Soetomo Surabaya for the period of August – October 2017.